2011
DOI: 10.1097/sap.0b013e3181fabc32
|View full text |Cite
|
Sign up to set email alerts
|

Integra Acellular Collagen as a Vascular Carrier for Skin Flap Prefabrication in Rats

Abstract: In this study, the feasibility of Integra acellular collagen used as a vascular carrier in skin flap prefabrication was examined. In all, 20 Sprague--Dawley rats were randomly divided into 3 groups. The saphenous vascular bundle was used as the vascular carrier. In group 1 (n = 8), an arteriovenous fistula was made by anastomosis of distal saphenous artery and vein. An Integra patch (2 × 3 cm²) was placed underneath the vascular bundle. In group 2 (n = 6), an Integra patch was placed on the top of the saphenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Studies have shown that angiogenesis initially appeared in DRT at day 7 following grafting, and peaked between day 7 and 14 (Shaterian et al 2009); DRT was found capable of active neovascularization and capable of serving as an effective dermal substitute (DS) in avascular wounds (Baynosa et al 2009); also DRT induced angiogenesis in flap prefabrication, and therefore could be used to support vascularization survival of a vascular prefabricated skin flap (Yan et al 2011).…”
Section: In Vivo Synthesis Of the Dermis Using The Cell-free Dermis Rmentioning
confidence: 99%
“…Studies have shown that angiogenesis initially appeared in DRT at day 7 following grafting, and peaked between day 7 and 14 (Shaterian et al 2009); DRT was found capable of active neovascularization and capable of serving as an effective dermal substitute (DS) in avascular wounds (Baynosa et al 2009); also DRT induced angiogenesis in flap prefabrication, and therefore could be used to support vascularization survival of a vascular prefabricated skin flap (Yan et al 2011).…”
Section: In Vivo Synthesis Of the Dermis Using The Cell-free Dermis Rmentioning
confidence: 99%
“…Blast injuries create diffuse areas of soft tissue destruction along with bacterial impregnation into wounds that directly correlate with increase rates of infection [36]. The large areas of uncovered defects in the soft tissue only serve to increase rates of infection.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple clinical applications and many anatomical sites that benefit from treatment with biologic scaffolds. Biologic scaffolds have been shown to facilitate limited tissue remodeling in a number of tissues in both preclinical animal models and human clinical studies [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The host response to biologic scaffold has been extensively characterized.…”
Section: Discussionmentioning
confidence: 99%